Urgency of Internal Academic Quality Audit Policy at Higher Education - Nofrita, Dewi; Rosyidi, Unifah; Karnati, Neti (Universitas Malikussaleh, 2019)
Universities and education now require quality assurance to ensure the quality of education. The implementation of a quality assurance system that already underway requires an internal audit process to ensure the quality process continues. Internal audit has an important role in management. Internal quality assurance is carried out through a cycle of establishing, implementing, evaluating, controlling, and increasing the standards of higher education.